Sport As a Factor in Forming an Attitude to Have a Healthy Lifestyle - Abdurakhmanov K.H.; Khamraev I.Y. (Zien Journals, 2024)
This study will focus on residents of the city of Chirchik aged 16 years and older, the relationship between physical education and sports, hobbies for sporting events and a healthy lifestyle.
Keywords: Health; youth; lifestyle; sports